Physical Activity And Financial Well-Being Among College Teachers In Kerala In The Aftermath Of Covid 19 Pandemic (Journal of Pharmaceutical Negative Results, 2023)
Covid 19 has forced everyone to curtail their outdoor physical activity and restrict themselves to indoors. With the commencement of online classes, college teachers found themselves isolated, stressed out and confined to homes. Teachers were initially worried about their ability to cope up with the new norms in education which was online teaching as well as concerned about their financial security. In order to deal with stress, many of the teachers turned to one or other healthy behaviors like joining for online Yoga, Zumba, Dance and other aerobic exercises. The study assessed the connection among physical activity patterns and financial well-being of college teachers in Kerala. The study focused on college teachers working in Autonomous, Government,  University Departments, and Self Financing and Government- Aided Colleges in Kerala. A sample of 250 college teachers was surveyed. The samples had a total service experience ranging from 1 to 30 years. The survey was conducted using IPAQ Questionnaire ,abbreviation of which is International Physical Activity Questionnaire, that consists of 7 questions, and Financial Wellbeing Scale, which consists of 10 questions. According to the results, 31.20 per cent of participants (N=78) were inactive with a MET score below 600, while 20 per cent (N=50) were 'minimally active' with a score ranging between 600 and 1499. The majority of teachers with MET scores above 1500 were in the "HEPA (Health enhancing physical activity)" category (N=122).  Financial well-being was found to be low among 1.20 per cent of teachers, average among 94 per cent of teachers, and high among 4.80 per cent of teachers. In addition, no significant correlation was found between MET total and financial well-being (-0.0148) among male college teachers, female college teachers (-0.049) and the total population of college teachers in Kerala (-0.098).